Synthesis, characterization and evaluation of lecithin-based nanocarriers for the enhanced pharmacological and oral pharmacokinetic profile of amphotericin B. Issue 42 (23rd September 2015) - Javed, Ibrahim; Hussain, Syed Zajif; Ullah, Irfan; Khan, Imran; Ateeq, Muhammad; Shahnaz, Gul; Rehman, Habib ur; Razi, Muhammad Tahir; Shah, Muhammad Raza; Hussain, Irshad
Abstract : Lecithin-drug hybrid nanocarriers (NCs) are demonstrated to enhance oral bioavailability and anti-parasitic potential for poorly water-soluble drugs. Abstract : We report the synthesis, characterization and evaluation of lecithin-drug hybrid nanocarriers (NCs) with enhanced oral bioavailability and anti-parasitic potential for poorly water-soluble drugs. Amphotericin B (AmB), a poor water-soluble drug with poor membrane penetrating ability, was selected as a model drug to demonstrate the potential of the lecithin-drug hybrid NCs. Lec-AmB NCs were prepared by the self-assembly of lecithin into nanoparticles (NPs) at a critical micellar concentration of 4 mg ml −1 and into liposomes at a critical liposomal concentration of 53 mg ml −1 in aqueous systems. The Lec-AmB NPs (200–300 nm) were further coated with polyethylene glycol ( M W 600) and Tween 20, whereas the liposomes (70–90 nm) were used as such for this study. The Lec-AmB NCs were evaluated for their ability to boost in vivo oral pharmacokinetic parameters in rabbits and in vitro anti-leishmanial activity against the promastigotes of Leishmania tropica . A reciprocal relationship was observed between the size and drug encapsulation efficiency of the NPs, but no such relationship was observed in the case of the liposomes. More importantly, the oral bioavailability and anti-leishmanial activity of Lec-AmB NPs was enhanced up to 21- and 6.3-fold, and 21- and 2-fold, respectively, in the case of the liposomes. The improvement in the bioavailability and anti-leishmanial activity is very significant compared to the deoxycholate complex of AmB (water soluble, injectable market product: Anfotericina FADA®), and this study, thus shows the promising potential of easy-to-prepare NCs with improved therapeutic efficiency using phosphocholine-based biocompatible surfactants.